Research Progress in Tritium Processing Technologies: A Review - Zhao, Ziqian; Sun, Yandong; Chen, Qi; Li, Tianchi; Liu, Fang; Yan, Taihong; Zheng, Weifang (Separations, 2025)
Recent advancements in tritium separation technologies have significantly improved efficiency, particularly through the integration of vapor phase catalytic exchange (VPCE), liquid phase catalytic exchange (LPCE), and combined electrolysis catalytic exchange (CECE) methods. Combining these techniques overcomes individual limitations, enhancing separation efficiency and reducing energy consumption. The CECE process, which integrates electrolysis with catalytic exchange, offers high separation factors, making it effective for high-concentration tritiated water treatment. Solid polymer electrolyte (SPE) technology has also gained prominence for its higher efficiency, smaller equipment size, and longer lifespan compared to traditional alkaline electrolysis. While electrolysis offers high separation factors, its high energy demand limits its cost-effectiveness for large-scale operations. As a result, electrolysis is often combined with other methods like CECE to optimize both energy consumption and separation efficiency. Future research will focus on improving the energy efficiency of electrolysis for large-scale, low-cost tritiated water treatment.